Impact of Organic Micropollutants Causing Mass Mortality of the Clams (Mactra aequisulcata) Due to Charactersitic Distribution at Karachi Coast, Pakistan: Micropollutants of the Clams (Mactra aequisulcata) (Biological Sciences - PJSIR, 2020)
Mass mortality of bivalve clams along with some other marine fauna was observed during the month of May 2016, mainly consisting of the clams (Mactra aequisulcata) of family Veneridae surfaced over the Clifton coast. The occurrence of mass mortality of the venerid clams Mactra aequisulcata and other marine life has been studied due to the toxicity of chlorinated hydrocarbons (DDTs, HCHs, hexa chloro benzene (HCB), chlordane, dieldrin (4-chlorophenyl), methanol (TCPMOH) and heptachlor epoxide and polychlorinated biphenyls (PCBs). Significant compositional characteristics of PCBs and DDTs were found in all dead clams and other fauna including fish (Johnius carutta), crabs (Portunus pelagicus), gastropods (Babylonia spirata), bivalves (Anadara antiquata), (Mactra aequisulcata) and the pen shell (Atrina pectinata) from Karachi coast, Pakistan. Mean concentrations (ranges) of organochlorine pesticides (OCPs) in crab (Portunus pelagicus) and fish samples were 1.1 (